CHRISTIAN CONCEPT OF SERVANT LEADERSHIP AND ITS RELEVANCE TO POLITICAL LEADERSHIP IN OYO STATE, NIGERIA (2023)
The Christian idea of Servant Leadership (SL), which connotes honouring God and serving humanity (John 13:1-5), is germane to political leadership globally, Nigeria inclusive. Existing studies on leadership concentrated largely on its types, styles and qualities, with scant attention paid to the Christian concept of SL in relation to politics in Oyo State. This study was, therefore, designed to examine the concept of SL from a Christian perspective in the context of political leadership in Oyo State. This was with a view to determining its nature and applicability to governance in the state. Robert Greenleaf’s Theory of Leadership was adopted as the framework, while the phenomenological design was used. The three senatorial districts in Oyo State were enumerated. Convenience sampling was employed to select from each senatorial districts of the local governments: Oyo South (Ibadan North and Ido), Oyo Central (Oyo West and Surulere) and Oyo North (Iseyin and Kajola). In-depth interviews were conducted with 120 purposively selected respondents (60 Christian politicians, 30 members of the clergy and 30 Christians representing the general public across the senatorial districts) based on their involvement in politics in the state. Six sessions of focus group discussions were held with the participants. The data were subjected to thematic analysis. The Christian concept of SL emphasises love for one’s neighbour as oneself, which is central to all laws (Mark 12: 31-32); justice, an important value to liberal political ideal in the fairness of judgment (Amos 5:24); and tolerance, accommodating contrary opinions and giving equal opportunity (2Tessallonians 3: 6-12). The concept stresses transparency, which should manifest in project execution and policy implementation (Nehemiah 5:14-16); and patriotism, which is genuine commitment to the well-being of one’s country and her people (Romans 13: 1-5). Since the creation of Oyo State in 1976, Christians have held many positions of authority, such as governor, deputy governor, speaker of the state assembly and commissioners. Commenting on the governance in the state, Christian politician respondents claimed that, despite the significant involvement of Christians in the state politics, the political atmosphere was laden with negative values, such as selfishness, greed and hatred, which contradict love. There was injustice in the distribution of amenities, as opposed to justice, as well as insensitivity to political differences and opinions, in contradistinction to tolerance; this led to political violence and insecurity. Members of the clergy submitted that there was also alleged corruption in the form of misappropriation and embezzlement of funds, which tainted transparency and engendered inept administration. Nonchalant attitude to development and people’s welfare, in disregard for patriotism, were also identified by the other respondent - Christians representing the general public. All this, culminated in infrastructure decay, like bad roads, schools and hospital facilities across the state, high level of poverty, unemployment, as well as a threat to human value well-being.Contrary to the Christian values inherent in servant leadership, many of the Christians holding political positions in Oyo State did not deploy efficiently those values to foster a favourable political atmosphere in the state